Lung macrophages utilize unique cathepsin K-dependent phagosomal machinery to degrade intracellular collagen - Fabrik, Ivo; Bilkei-Gorzo, Orsolya; Öberg, Maria; Fabrikova, Daniela; Fuchs, Johannes; Sihlbom, Carina; Göransson, Melker; Härtlova, Anetta (Life science alliance, 2023)
Resident tissue macrophages are organ-specialized phagocytes responsible for the maintenance and protection of tissue homeostasis. It is well established that tissue diversity is reflected by the heterogeneity of resident tissue macrophage origin and phenotype. However, much less is known about tissue-specific phagocytic and proteolytic macrophage functions. Here, using a quantitative proteomics approach, we identify cathepsins as key determinants of phagosome maturation in primary peritoneum-, lung-, and brain-resident macrophages. The data further uncover cathepsin K (CtsK) as a molecular marker for lung phagosomes required for intracellular protein and collagen degradation. Pharmacological blockade of CtsK activity diminished phagosomal proteolysis and collagenolysis in lung-resident macrophages. Furthermore, profibrotic TGF-β negatively regulated CtsK-mediated phagosomal collagen degradation independently from classical endocytic-proteolytic pathways. In humans, phagosomal CtsK activity was reduced in COPD lung macrophages and non-COPD lung macrophages exposed to cigarette smoke extract. Taken together, this study provides a comprehensive map of how peritoneal, lung, and brain tissue environment shapes phagosomal composition, revealing CtsK as a key molecular determinant of lung phagosomes contributing to phagocytic collagen clearance in lungs.
Keywords: Collagen; plíce; lidé; kolagen; Cathepsin K; Lung; Macrophages; kathepsin K; Phagosomes; makrofágy; fagozomy; Humans